2006
DOI: 10.1243/09544119jeim67
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Sintering of Hydroxyapatite Reinforced Polyethylene Composites for Bioactive Implants and Tissue Scaffold Development

Abstract: Selective laser sintering (SLS) has been investigated for the production of bioactive implants and tissue scaffolds using hydroxyapatite (HA) reinforced polyethylene (HDPE) composites with the aim of achieving the rapid manufacturing of customised implants. Single layer and multilayer block specimens made of HA-HDPE composites with 30 vol% and 40 vol% HA were sintered successfully using a CO 2 laser sintering system. Laser power and scanning speed had a significant effect on the sintering behaviour. The degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 19 publications
0
64
0
1
Order By: Relevance
“…Some groups were able to directly fabricate bioceramic bone implants using an experimental SLS system [2,3], however, to process bioceramics a thermoplastic polymer functioning as a binder material is usually required, as the lasers used in typical commercial SLS systems are unable to fuse ceramic particles together. Several biocompatible polymers have been used for SLS fabrication of scaffolds, including polyethylene, polyetheretherketone, polycaprolactone, polylactide glycolide, polyvinyl alcohol and their composites with hydroxyapatite and other bioceramics [4][5][6][7][8][9][10][11][12]. However, much of this research has only demonstrated the feasibility of fusing powder particles together, and not the fabrication of complex predesigned 3D structures.…”
Section: Introductionmentioning
confidence: 99%
“…Some groups were able to directly fabricate bioceramic bone implants using an experimental SLS system [2,3], however, to process bioceramics a thermoplastic polymer functioning as a binder material is usually required, as the lasers used in typical commercial SLS systems are unable to fuse ceramic particles together. Several biocompatible polymers have been used for SLS fabrication of scaffolds, including polyethylene, polyetheretherketone, polycaprolactone, polylactide glycolide, polyvinyl alcohol and their composites with hydroxyapatite and other bioceramics [4][5][6][7][8][9][10][11][12]. However, much of this research has only demonstrated the feasibility of fusing powder particles together, and not the fabrication of complex predesigned 3D structures.…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials (Ti/Al 3003) and Al 3003 matrix material were used to Table 6 [63,[67][68][69][70].…”
Section: Structural Compositesmentioning
confidence: 99%
“…Hydroxyapatide (HA), for instance, is known for its bioactive behaviour and osteoconductivity. HA has been blended with PCL, PE, PEEK, and polyvinylalcohol (PVA), and the compound powders have been processed via laser sintering [6,7,13,14].…”
Section: Compositesmentioning
confidence: 99%
“…It appeared that this was rather due to the high HA content than to the nature of the composite powder, as in this case the HA content was 80 wt.-% and the amount of polymeric binder phase was too small to generate bonding between the particles. Maximum concentrations of hydroxyapatide (HA) in composites were investigated by Hao et al [13], Savalani et al [17], and Zhang et al [18]. Polyethylene and polyamide were used as binders, and concentrations of up to 50 % of HA were achieved.…”
Section: Compositesmentioning
confidence: 99%